The Influence of Global Talent Management on Employer Attractiveness: An Experimental Study. (August 2013) - Ewerlin, Denise
Due to the intensifying "war for talent", companies are increasingly looking to position themselves as attractive employers. They are also increasingly communicating their global talent management (GTM) programs through their websites and job advertisements. However, to date, there is a dearth of research as to whether the presence of GTM programs increase the attractiveness of companies for talent, and to what extent this effect is shaped by the contents of GTM programs and the cultural background of talented individuals. This paper seeks to overcome these deficits by presenting an experimental investigation of the influence of GTM programs on employer attractiveness and how this is moderated by culture. It shows that employer attractiveness is not influenced by GTM programs per se, but rather by the contents of GTM programs and the cultural background of talented individuals.